Role of 18F-FDG-PET/CT in an AML-M5a Subtype Patient with Rare Constellation of Hemophagocytic Lymphohistiocytosis & Bilateral Multiple Breast Chloromas - Shrinivas, Yuvan; Palaniswamy, Shanmuga Sundaram; Subramanyam, Padma (World Journal of Nuclear Medicine, 2024)
We report a treated case of acute myeloid leukemia (AML-M5a subtype) with monocytic differentiation (AMoL) presenting with fever and body pains. Initial 18F-FDG-PET/CT (18F-flurodeoxyglucose positron emission tomography/computed tomography) identified multiple lymph nodal, and marrow lesions. Biopsy confirmed hemophagocytic lymphohistiocytosis (HLH). Post HLH treatment, follow-up PET/CT demonstrated unsuspected FDG avid bilateral breast lesions (n = 5), which proved to be chloromas, that is, extranodal manifestation of AML. 18F-FDG-PET/CT has helped not only in identifying the various sites of disease involvement but also in guiding the sites for biopsy. Finally, 18F-FDG-PET/CT was useful in monitoring therapy response for both these coexisting pathologies, which are said to be resistant to treatment based on FLT3-ITD tyrosine kinase-3 internal tandem duplication mutation positivity and high-grade AML status. This case represents a rare constellation of different etiologies that needed to be differentiated. It also emphasizes the challenges in interpreting PET/CT findings, especially in difficult clinical scenarios. Disease distribution in HLH/presence of chloromas, etc., can mimic stage IV lymphoma in a known case of AML. So the nuclear medicine physician should be aware of the different complications in the background of AML, especially in patients with poor prognostic factors.
Keywords: AML; hemophagocytic lymphohistiocytosis; fever; whole-body 18F-FDG-PET/CT; chloromas; breast